FAMILY POLICY AND ITS REALIZATION TRENDS IN LITHUANIA FOR 2005–2012 - Gavelis, Vytautas; Visockas, Evaldas (Ekonomika, 2013)
Abstract. The purpose of the article is an overview of the objectives and criteria of theclassification used in state family policy in the sphere of economic relations, a discussion of family policy types and sub-types, relations between forms and types, and their characteristics in contemporary conditions. It discloses the significance of a systemic approach to family policy, emphasizes that family policy can be investigated both as a separate system and as a subsystem emphasizes that a particular family policy must reflect the inherent relations of the subsystems and components, i.e. an implementation area of family policy, its targets, goals, priorities, directions and state’s ability to provide economic support draws attention to the fact that family policy should be associated not only with the family as a general institution but also with individual family forms, describes the trends of public financial social assistance for families raising children and for poor residents in 2005–2012.Key words: family policy, types of family policy, family forms, benefits for families raising children, financial social assistance for poor residents